Antibacterial Activity and Interaction Effects of Litsea Cubeba Fruit Essential Oil and Chitosan Against Food-Borne Bacteria - Nguyen, Hai Van; Phan, Thanh Tam; Chu, Ky Son; Nguyen, Thi Thu Trang (JST: Engineering And Technology For Sustainable Development, 2021)
The aims of this study were to investigate the antibacterial activity and interaction effect of Litsea cubeba fruit essential oil (EO) and chitosan (CTS) against food-borne bacteria. The zone inhibition of EO, CTS and EO-CTS mixture against Escherichia coli ATCC 25922, Salmonella Typhimurium ATCC 14028, Staphylococcus aureus ATCC 25923 and Bacillus cereus ATCC 13061 ranged from 39.0-57.3 mm; 11.7-15.5 mm and 29.7-39.3 mm, respectively. The minimum inhibitory concentration of EO and CTS were 5.53 mg/mL and from 600-800 ppm, respectively. The synergistic effects were found when EO and CTS were used in combination with fractional inhibitory concentration values ranging from 0.62-0.67. Indeed, the concentration of EO and CTS were decreased 6-8 and 2 times in combination comparing with individual treatment, respectively. The obtained results demonstrated the potential application of EO-CTS mixture in food preservation.